Effects of palm oil fuel ash (POFA) on concrete towards chloride resistance - Siti Masarah , Mohd Said (2012)
Nowadays, high durability concrete and environmental friendly approach toward building, structure and other concrete construction is in demand. The used of Portland cement also increase CO 2 to environment. In other hand, there are also issues on excess side product from palm oil production which is palm oil fuel ash (POFA) which also can contribute to environmental problem. POFA is a waste consist of fibers, shells and empty fruit bunches being incinerate. POFA need to be fully utilized in more benefit ways and since properties of POFA slightly the same with Portland cement, this give an idea to use it as replacement of cement. Besides that, composition of POFA could resist toward chloride reaction. So, by using POFA as replacement for Portland cement, it expected that there will be reduction of CO2 and excess POFA in our environment and more durability concrete can be produced. Chloride ingression inside the concrete structure and cause steel structure and rebar to become rust and weaken the structure as a whole. In this research, there will be test on chloride resistance and porosity as indicator of chloride ingression towards the concrete. Preparation of sample including batching, mixing and casting was earlier prepared before testing being conduct. 24 cubical concrete samples and 24 cylindrical concrete samples being prepared and cured for 28 days. Chloride resistance test including salt ponding, open circuit potential (OCP) and impress voltage while porosity test involving vacuum saturation method. Result from this test will be indicator of POFA effectiveness towards chloride resistance.